Perceived workplace culture as an antecedent of job stress : the mediating role of work-family conflict. - Ahmad, Aminah; Omar, Zoharah (Science Publications, 2010)

(untitled)
Few studies have tested the mediating effect of work-family conflict on the relationship between workplace culture and job stress. Approach: This study tested a mediation model consisting of job stress as the dependent variable, perceived family-supportive work culture as the independent variable and work-family conflict as the mediator. Data were gathered from 693 employees from private service organizations in the Klang Valley, Malaysia, using self-administered questionnaires. The data were analyzed using correlation and multiple regression analyses. Results: Results of correlation analysis revealed that perceived family-supportive work culture was related to work-family conflict and job stress and work-family conflict was related to job stress. Results of a series of multiple regression analyses indicated that work-family conflict partially mediates the relationship between perceived family-supportive work culture and job stress. Conclusion/Recommendations: Employees who perceive that their organizations are family supportive seem to experience less stress at the workplace and less work-family conflict. Employers should take into consideration employees’ perceptions of how supportive the organization is of their family needs as a factor that could reduce the experience of work-family conflict and job stress. Employers should also look into the possibility of developing programmes to assist employees in managing work-family roles.